Management of viral oral ulcers in children using Chinese herbal medicine: A report of two cases. (June 2017) - Lee, Yi-Chiao; Wang, Ting-Hao; Chen, Shih-Yu; Lin, Hsiang-Ling; Tsai, Ming-Yen
Abstract: Objective: Viral oral ulcers are common presentations in pediatric clinics. Although self-limiting, painful ulcerative lesions and inflamed mucosa can decrease oral intake and lead to dehydration. Despite the widespread use of Chinese herbal medicine (CHM) for pediatric upper respiratory disease in Taiwan, there is little evidence for its effectiveness as an antipyretic or in aiding ulcer healing for children with viral oral ulcers. We report two cases of children who presented with viral oral ulcers to illustrate the potential efficacy of CHM treatment in recovery from herpangina (HA) and herpetic gingivostomatitis (HGS). Clinical features and outcome: A 10-year-old girl with HA presented with an acute febrile illness associated with small vesicular or ulcerative lesions on the posterior oropharyngeal structures. The family refused western medicine due to a prior anaphylactic skin rash when she had taken sulfa drugs. The other patient was a 4-year-old boy with complaints of painful ulcers and hemorrhagic crusts on the lips. He was diagnosed with HGS and had received ibuprofen and supportive treatments such as hydration and local anesthesia spray for days, characterized by fever, anorexia, and nausea to no effect. Because the patients were suffering from the damp-heat syndrome according to Traditional Chinese Medicine (TCM) differentiation, both were treated using the same herbal formulas powder prescription, named Liang Ge San (LGS) and Gan Lu Xiao Du Dan (GLXDD). After several days of CHM treatment, the oral ulcers were in regression. Follow-up of the frontal view in both patients showed satisfactory disappearance of the sick furred tongue. Conclusions: The results of these case reports show that the early prescription of CHM is an effective modality of alternative treatment for viral oral ulcers. To our knowledge, this is the first report of CHM treatment hastening the recovery from febrile disease with viral oral ulcers in Taiwan. Future experimental studies to determine the definitive mechanism and clinical trials are warranted.